PENGARUH PEMBERIAN TEPUNG AZOLLA (Azolla microphylla) TERHADAP BOBOT BADAN DAN KONVERSI PAKAN AYAM KAMPUNG FASE BROODING - Fajri Nurrohman; Sari Tuswati; Sulistyaningtyas; Doso Sarwanto (Fakultas Peternakan. Unwiku, Purwokerto, 2024)
The research titled The Effect of Azolla Meal (Azolla microphylla) Supplementation on the Body Weight and Feed Conversion of Village Chickens in the Brooding Phase was conducted from June 7 to June 21, 2024. This study aimed to determine the effect of Azolla meal supplementation on body weight and feed conversion in village chickens during the brooding phase. The research material used consisted of 60 one-day-old DOC village chickens. Azolla meal was administered over a two-week period. The DOC chickens were placed in experimental cages measuring 30 cm x 30 cm x 40 cm, with 20 units in total. This study employed an experimental method with a Completely Randomized Design (CRD) in a single factor pattern consisting of four treatments: P0 (control), P1 (2% Azolla meal), P2 (4% Azolla meal), and P3 (6% Azolla meal). Each treatment had five replications, resulting in 20 experimental units. Each unit contained three chickens, totaling 60 DOC village chickens. Parameters measured included body weight and feed conversion. The average body weights of the chickens with 0%, 2%, 4%, and 6% Azolla meal supplementation were 77.58, 77.82, 80.64, and 78.56 grams, respectively. The average feed conversion rates with 0%, 2%, 4%, and 6% Azolla meal supplementation were 6.677, 6.195, 5.974, and 6.016, respectively. The addition of Azolla meal at 0%, 2%, 4%, and 6% doses resulted in non-significant differences in body weight and feed conversion